Settlement of Brand Rights Disputes Through the Commercial Court in Indonesia: Study of Surabaya Court Decision - I Gede Mahatma Yogiswara; Lesza Leonardo Lombok; Asrul Ibrahim Nur; I Gusti Bagus Indra Kumara; Ni Nyoman Sri Purnama Sutianti (Universitas Muhammadiyah Malang, 2022)
Brands play a significant role in economic development because they help consumers identify the origin of a product or service. Brand ownership is acknowledged at the time of brand registration with the Directorate General of Intellectual Property. The first prerequisite for registering a brand is ensuring that it possesses all of its attributes. Therefore, some characteristics distinguish it from other brands. Despite these regulations, brand infringements still occur. One of them is the disagreement between PT. Gudang Garan and PT. Gudang Baru, whose brands are comparable. Therefore, a study on Indonesian law enforcement in resolving brand issues is required. The current study employed normative legal research and normative juridical methodologies. Using descriptive qualitative data analysis, the study focused on laws and regulations. The Surabaya Commercial Court determined, based on a dispute between PT. Gudang Garan and PT Gudang Baru, that PT. Gudang Baru breached Article 21 Paragraph 1 of Law No. 20 of 2016, declaring the Gudang Baru brand comparable to the well-known Gudang Garan brand. As a result, the Gudang Baru brand was revoked, and to ensure a deterrent effect, DGKI ordered any application for registration of a brand that resembles PT. Gudang Garan be denied.